2015
DOI: 10.3390/jintelligence3040121
|View full text |Cite
|
Sign up to set email alerts
|

John Carroll’s Views on Intelligence: Bi-Factor vs. Higher-Order Models

Abstract: The development of factor models is inextricably tied to the history of intelligence research. One of the most commonly-cited scholars in the field is John Carroll, whose three-stratum theory of cognitive ability has been one of the most influential models of cognitive ability in the past 20 years. Nonetheless, there is disagreement about how Carroll conceptualized the factors in his model. Some argue that his model is best represented through a higher-order model, while others argue that a bi-factor model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 67 publications
3
86
0
1
Order By: Relevance
“…Other researchers maintained that the bifactor model better represents Spearman's (1904Spearman's ( , 1927 and Carroll's (1993) conceptualizations of intelligence (Beaujean, 2015;Frisby & Beaujean, 2015;Brunner et al, 2012;Gignac, 2006Gignac, , 2008Gignac & Watkins, 2013;Gustafsson & Balke, 1993). Beaujean (2015) noted that Spearman's conception of general intelligence was of a factor 'directly involved in all cognitive performances, not indirectly involved through, or mediated by, other factors' (p. 130), and that 'Carroll was explicit in noting that a bi-factor model best represents his theory' (p. 130). Murray and Johnson (2013) suggested that bifactor models might benefit from statistical bias when compared to higher-order models by better accounting for unmodelled complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers maintained that the bifactor model better represents Spearman's (1904Spearman's ( , 1927 and Carroll's (1993) conceptualizations of intelligence (Beaujean, 2015;Frisby & Beaujean, 2015;Brunner et al, 2012;Gignac, 2006Gignac, , 2008Gignac & Watkins, 2013;Gustafsson & Balke, 1993). Beaujean (2015) noted that Spearman's conception of general intelligence was of a factor 'directly involved in all cognitive performances, not indirectly involved through, or mediated by, other factors' (p. 130), and that 'Carroll was explicit in noting that a bi-factor model best represents his theory' (p. 130). Murray and Johnson (2013) suggested that bifactor models might benefit from statistical bias when compared to higher-order models by better accounting for unmodelled complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Reise (2012) and Canivez (2016) noted several advantages of bifactor models including the direct influences of the general factor are easy to interpret, both general and specific influences on indicators (subtests) can be examined simultaneously, and the psychometric properties necessary for determining scoring and interpretation of subscales can be directly examined. Gignac (2006) also noted that the bifactor model can be considered more conceptually parsimonious because it specifies a unidimensional general factor and this model seems more consistent with Spearman's (1927) and Carroll's (1993) models of intelligence (Beaujean, 2015).…”
mentioning
confidence: 85%
“…For example, Gignac (, ) contended that the most substantial factor of a battery of tests (i.e., g ) should be directly modelled, whereas its full mediation in the higher‐order model demands explicit theoretical justification; that is, a rationale is needed for why general intelligence should directly influence group factors but not subtests. Other researchers have argued that a bifactor model better represents Spearman's () and Carroll's () conceptualizations of intelligence than the higher‐order model (Beaujean, ; Beaujean, Parkin, & Parker, ; Brunner, Nagy, & Wilhelm, ; Frisby & Beaujean, ; Gignac, , ; Gignac & Watkins, ; Gustafsson & Balke, ). Beaujean () elaborated that Spearman's conception of general intelligence was of a factor ‘that was directly involved in all cognitive performances, not indirectly involved through, or mediated by, other factors’ (p. 130) and noted that ‘Carroll was explicit in noting that a bi‐factor model best represents his theory’ (p. 130).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have argued that a bifactor model better represents Spearman's () and Carroll's () conceptualizations of intelligence than the higher‐order model (Beaujean, ; Beaujean, Parkin, & Parker, ; Brunner, Nagy, & Wilhelm, ; Frisby & Beaujean, ; Gignac, , ; Gignac & Watkins, ; Gustafsson & Balke, ). Beaujean () elaborated that Spearman's conception of general intelligence was of a factor ‘that was directly involved in all cognitive performances, not indirectly involved through, or mediated by, other factors’ (p. 130) and noted that ‘Carroll was explicit in noting that a bi‐factor model best represents his theory’ (p. 130). In fact, Jensen and Weng () suggested a bifactor model as the first step in their strategy for identifying general intelligence (Jensen & Weng, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation